EFEKTIFITAS PEMBELAJARAN KOOPERATIF TIPE NHT DENGAN PENDEKATAN KONTEKSTUAL PADA PEMBELAJARAN BANGUN RUANG SISI DATAR - Pradana, Lingga Nico (Premiere Educandum, 2015)
The purpose of this research was to determine the effect of learning models to studentachievement. Learning models compared between NHT-CTL, NHT and direct instruction.Method of research used quasi experimental with the factorial design of 3x1. Populationof this research was all students class VIII in SMP Negeri at Madiun City. The samplingtechnique using a stratified cluster random sampling. Samples in this research were 266students with 91 students as experimental class I, 88 students as experimental class II and87 students as control class. Data collection methods used documentation andtest.Hypothesis testing was performed using one-way analysis of variance with unequalcells. Based on the results of hypothesis testwere concluded that NHT-CTL learningmodel gave better achievement than NHT learning model and direct instruction, whileNHT learning model and direct instruction gave the same achievement. Keywords: NHTlearning model, CTL approaches, learning achievement